The dependence of the early and long-term prognosis in patients with chronic heart failure with preserved left ventricular ejection fraction from the initial serum sodium level - Svitlyi, M. O. (My University, 2024)
Aim. To study the dependence of the early-term (1 year) and long-term (5 years) prognosis in patients with chronic heart failure (CHF) of ischemic origin with preserved left ventricular ejection fraction (LVEF) depending on hyponatremia.
Keywords: тези доповідей